Pengaruh Brand Personality Shopee terhadap Minat Menggunakan Fitur Shopee Pay Later pada Generasi Milenial Surabaya - Tiara Rose Agrippina; Catur Suratnoaji (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
Marketing communication is all forms of activity to disseminate information and persuade consumers or customers directly or indirectly about an item and brand. SHOPEE made an innovation by launching the latest feature, namely the online loan feature in its application. In this study, the author will continue to examine all millennial generations, both the early and late millennial generations. The type of research used is quantitative. The city of Surabaya was chosen as the research location because the city of Surabaya is the center of the capital and economy in East Java Province. The analysis technique used is descriptive analysis and multiple linear regression analysis techniques to determine the effect of brand personality on purchase intention. The sample in this study was 100 millennial generation respondents from 5 regions in Surabaya. The analysis used was SPSS. Based on the results of research and discussion that Brand Personality has a significant effect on intention to use.